A study of the effect on work stressor towards employees commitment to change at Pejabat Daerah Dan Tanah Jerantut, Pahang / Nur Syafika Nazaruddin - Nazaruddin, Nur Syafika (2020)
The purpose of this research was to investigate the affect on work stressor towards employee commitment to change. The researcher used three elements of work stressor; role overload, role conflict and role ambiguity, which the objectives were to identify the affect of work stressor towards employees' commitment to change. Apart from that, the researcher used a correlation test to evaluate the relationship between these variables. This research study was conducted at Pejabat Daerah dan Tanah Jerantut, Pahang (PDTJ), with 60 questionnaires was forwarded via google form to all level department management (Units). Plus, the questionnaires that have been forwarded via google form also as the main tools for data collection. The Statistical Package in the Social Science Software (SPSS) was used to interpret the finding. The data collected were analyzed using frequency distribution tables and percentages, mean and standard deviations and Pearson correlations. Based on the data obtained, it can be inferred that the most significant affect the work stressor towards employees' commitment to change was role ambiguity. Based on a comprehensive review of the data obtained, the subsequent proposal was made the organization should focus on any work stressor that related with and use it as to enhance their commitment to change.